Pengaruh Ekstra Lidah Buaya ( Aloe vera) Sebagai ZPT Alami untuk Pertumbuhan Tanaman Kacang Tanah (Arachis hypogaea) - Srg, Rianto Joni; Hrp, Rahmi Sari (UNIVERSITAS LABUHANBATU, 2023)
Aloe Vera plants (Aloe vera) contain minerals including selenium, calcium, magnesium, potassium and several enzymes of sugar, fatty acids, and also growth hormones, namely auxin and gibberellin. This study was conducted to determine the extra effect of Aloe vera on the growth of peanut plants. The study was conducted by providing treatment in the form of watering peanut plants with Aloe vera solution exta at several different concentrations and controls as a reference. The treatment was carried out for 14 days and observation of the growth of green bean plants was carried out every 3 days. The data obtained were tested using One-Way ANOVA, Then analyzed descriptively. The results showed that peanut plants had significantly different growth in the 10% gel concentration treatment which resulted in the highest plant height, while the number of leaves, leaf area, and stem diameter did not have a significant effect. Keywords: aloe vera, growth, ZPT